Upaya Pemenuhan Kebutuhan Logistik Pertahanan pada Masa Revolusi di Sumatera Barat, 1945-1949 - Hutagalung, Albertus; Nopriyasman, Nopriyasman; Asnan, Gusti (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This study investigates efforts to meet the needs of defense logistics during the Indonesian Revolutionary War in West Sumatra. The research emphasizes the strategic role of West Sumatra in the struggle for independence. The main question is how local fighters and communities managed to secure and distribute essential supplies, such as food, weapons, and ammunition, under inadequate conditions. Using historical methods, this study analyzes primary and secondary sources, including archival documents and official reports. The qualitative analysis aims to reconstruct the logistics operations and adaptive measures undertaken by the local population. The findings show that despite limited local resources, fighters employed a variety of innovative strategies. These efforts were crucial in maintaining supply chains and ensuring the sustainability of defense logistics. In conclusion, this study argues that success in war is largely determined by the ability to manage and meet logistical needs.